Payout policies and closed-end fund discounts: Signaling, agency costs, and the role of institutional investors - Jay Wang, Z.; Nanda, Vikram (Journal of Financial Intermediation, 2011)
The adoption of a managed distribution policy or plan (MDP) by closed-end funds appears effective in dramatically reducing, even eliminating, fund discounts. We investigate two possible explanations: the signaling explanation proposed in the literature, that the MDP serves as a positive signal of future fund performance, and an alternative explanation based on agency costs. Our results indicate that signaling is, at best, only part of the explanation and that the evidence is generally more consistent with the agency cost hypothesis. For funds adopting aggressive payout targets of 10% (median target) and above, discounts tend to disappear, though there is no discernible improvement in NAV performance. Consistent with the agency cost hypothesis, it is often pressure from institutions/large shareholders that leads to the adoption of aggressive payout policies. Moreover, aggressive-MDPs are associated with a decrease in fund size and managerial fees. Suggestive of their activist role in MDP adoptions and/or informed trading, institutions – especially ones that are Value oriented – tend to build-up their holdings in a fund prior to the adoption of an aggressive-MDP, and liquidate their positions once the price rises.